A Debreceni Egyetem Gazdaságtudományi Karának Controlling és teljesítménymenedzsment szakirány kurzusainak értékelése - Markos, Valéria; Tóth, A. D.; Kocsis, Imre; Máthé, Endre; Juhász, Csaba; Bácsné Bába, Éva; Fenyves, Veronika (International Journal of Engineering and Management Sciences, 2017)
It is of major importance for the Faculty of Economics and Business of the University of Debrecen to become familiar with the opinion of students about the education carried out at the University, therefore particular attention is given to the feedback of students related to education. Measurement and evaluation/reviews serve multiple purposes. Students may – if explicit written consent of the lecturer is provided – get to know the opinion of their fellow students about each course, lecturers may receive feedback about the reputation of their courses, the University and Faculties may acquire information about the overall opinion of their students about the training. Feedback is basically suitable for supporting the work aimed at the improvement of training quality. In the scope of present study the reviews submitted by the students of the Controlling and performance specialisation within the Management and Organisation course are introduced.